Anatomical study of all carpal and adjoining bones of the wrist using 3D CT reconstruction –Finding the ultimate biomechanical theory - Gill, Dominik; Lyer, Stefan; Alexiou, Christoph; Fried, Frederik; Buder, Thomas; Neuhuber, Winfried; Jacxsens, Matthijs; Horch, Raymund E.; Arkudas, Andreas (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Background: The complex interplay of single wrist bones acting in combination with their ligamentous connections is still not fully understood. In this regard various theories exist, divisible in columnar and ring/row theories. The object of this study was to examine the mobility of the individual carpal bones as well as the ulna and metacarpals relative to each other in wrists of cadaveric hands using CT scans. Methods: The regular wrist mobility of a total of 21 cadaveric hands was examined by CT imaging in neutral position, radial/ulnar abduction as well as wrist flexion and extension. The data were evaluated as 3D models by using a standardized global coordinate system and object coordinate systems. Rotation and translation of each carpal bone as well as radius/ulna and all metacarpal bones were evaluated. Results: The principal motion took place in the carpus between the radius and the proximal carpal row followed by the midcarpal joint and the carpometacarpal joints and not mainly between the individual bones of a row. The scaphoid moves out of its row aggregate mainly during flexion and adapts to the motion of the distal carpal row. The trapezium and first metacarpal bones play a specific role detached from the remaining bones. Conclusions: With this study, a better understanding of the motion of the individual bones of the carpus, the metacarpals and the radius/ulna is shown. The study supports the row theory, where most motion takes place between the individual rows and not between the carpal bones, leaving the scaphoid and the first ray in a special role between the rows.
CRIS-Team Scopus Importer:2022-03-18
Keywords: 3-dimensional Computed Tomography; Biomechanical Theory; Wrist